Development of security camera combined beacon signal for transmission of disaster and crime situation as well as tracking location - Ho Kim, Yong; Won Bang, Gul (International Journal of Engineering and Technology, 2018)
Background/Objectives: There is the needs for the service to send text message of location to guardian and acquaintance, and police station by waving smartphone quicklyin emergency circumstances that are on the cards at the moment.Methods/Statistical analysis: Android marshmallow version 6.0.1 in Samsung galaxy S6 smartphone is used to test beacon convergent security camera. Used application is Beacon Finder and test result of address and UUID in beacon is normally generated and found that the values have normal output.Findings: Development of security camera combined beacon signal for transmission of disaster and crime situation as well as tracking location is development in this study. Design of firmware for beacon signal transmitting device is implemented to achieve the goal. CCTV security camera with beacon signal through circuit design of CCTV and beacon interface is manufactured. Circuit design of beacon signal transmitting device based on Bluetooth 4.0 is implemented to develop an independent device.Improvements/Applications: Development of security camera combined beacon signal for transmission of disaster and crime situation as well as tracking location is development in this study. Design of firmware for beacon signal transmitting device is implemented to achieve the goal.Foundation technique in the field of home network, USN, and LED lighting control is possible to secure as various technique element for ubiquitous related convergence technology in the field of home electronic appliance with digital information is includedÂ